RESEARCH ON INFLUENCING FACTORS OF ADOLESCENTS’ SPORTS HEALTH BEHAVIORS IN SOCIAL ECOLOGY - Song,Weijun (2021)
ABSTRACT Introduction: Physical exercise has a positive effect on the health of individuals. Long-term sedentary behavior can induce coronary heart disease, hypertension, diabetes, and other chronic diseases. Lack of physical exercise has become the fourth leading cause of death worldwide. Therefore, youth sports are very important for physical health. Objective: To systematically reveal the influencing factors of adolescents’ physical exercise and improve the effectiveness of interventions on adolescents’ physical exercise behaviors, this article is based on social ecology theory to study the structural model of adolescents’ physical exercise factors. Methods: The thesis considers factors affecting adolescent physical exercise as the research object and uses literature method, questionnaire survey, mathematical statistics, etc., to construct a structural model of factors affecting youth physical exercise, including four primary indicators and 19 secondary indicators. Results: Adolescent physical exercise is affected by the school, family, social and personal factors. Among them, family factors have the greatest impact on young people's physical exercise. Personal factors rank second, school factors, and social factors rank third. Among the family factors, the major influences on youth physical exercise are “parental support,” “parents’ cognition of physical exercise,” and “parental exercise habits.” Conclusions: The influencing factors of adolescent physical exercise involve four aspects: family, society, school, and self. Family factors have the greatest impact on adolescent physical exercise, and personal factors are the second, school factors, and social factors are the third. Level of evidence II; Therapeutic studies - investigation of treatment results.